2011
DOI: 10.1016/j.jsp.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family processes on school achievement as moderated by socioeconomic context

Abstract: This longitudinal study examined a model of early school achievement in reading and math, as it varies by socioeconomic context, using data from the NICHD Study of Early Child Care and Youth Development. A conceptual model was tested that included features of family stress, early parenting, and school readiness, through both a single-group analysis and also a multiple-group analysis. Latent profile analysis was used to identify subgroups of more advantaged and less advantaged families. Family stress and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 71 publications
3
28
0
5
Order By: Relevance
“…The lack of a matching consistent pattern in the maternal sensitivity results across predictors answers our research question concerning the direct/mediated influence of early caregiving features. These results may be explained by sociodemographic considerations in the SECCYD, as reported by Oxford and Lee (2011), indicating that maternal sensitivity seems to play a more significant protective role for children at socioeconomic disadvantage, hence when considering the broader SECCYD sample, any such effects may dissipate (see also Raver, 2004). …”
Section: Discussionmentioning
confidence: 97%
“…The lack of a matching consistent pattern in the maternal sensitivity results across predictors answers our research question concerning the direct/mediated influence of early caregiving features. These results may be explained by sociodemographic considerations in the SECCYD, as reported by Oxford and Lee (2011), indicating that maternal sensitivity seems to play a more significant protective role for children at socioeconomic disadvantage, hence when considering the broader SECCYD sample, any such effects may dissipate (see also Raver, 2004). …”
Section: Discussionmentioning
confidence: 97%
“…Time spent with deviant peers increases offending behaviors by providing the techniques, motives, and reinforcement for committing crime (Sutherland, 1947). Studies continue to find that a close relation with deviant peers and isolation from prosocial peers affect drug use and criminal involvement (Haynie, 2003; Oxford & Lee, 2011; Simons & Robertson, 1989). Studies on social networks have found that peer affiliations and friendship networks can change over time (Giordano, Cernkovich, & Holland, 2003; Hawkins & Fraser, 1987; Warr, 1998; Wright & Cullen, 2004).…”
Section: What Do We Know About Criminogenic Needs?mentioning
confidence: 99%
“…Martínez-Pons (1996) define o envolvimento da família no processo de autorregulação através de quatro condutas: modelado (quando o comportamento dos pais oferece exemplos de autorregulação), estimulação e apoio motivacional (quando os pais favorecem a persistência dos filhos perante condições adversas), facilitação ou ajuda (quando os pais facilitam a aprendizagem facultando recursos e meios) e recompensa (quando os pais reforçam os comportamentos). Neste quadro desenvolvimental da criança ganham importância as habilitações escolares parentais, uma vez que diferenciam as estratégias educativas e a forma de interação pais-filhos (Alves et al, 2014;Oxford & Lee, 2011). Pais com elevadas habilitações escolares, comparativamente a pais com habilitações mais baixas, aparecem associados a expetativas mais positivas, a um ambiente e experiências mais estimulantes, e a um maior compromisso e preocupação com a vida escolar dos filhos, o que se repercute no desenvolvimento cognitivo e autonomia e, consequentemente, na aprendizagem da criança (Bradley & Corwyn, 2002;Bradley, Corwyn, Burchinal, McAdoo, & Coll, 2001;Cianci, Orsini, Hulbert, & Pezzuti, 2013;Davis-Kean, 2005;Dumka, Gonzales, Wheeler, & Millsap, 2010;Rindermann, Michou, & Thompson, 2011).…”
Section: Papel Determinante Da Famíliaunclassified